Pembrolizumab for advanced cervical cancer: safety and efficacy. Issue 2 (1st February 2021) - De Felice, Francesca; Giudice, Elena; Bolomini, Giulia; Distefano, Maria Grazia; Scambia, Giovanni; Fagotti, Anna; Marchetti, Claudia
ABSTRACT: Introduction : Pembrolizumab is an immune checkpoint inhibitor with high specificity for binding to the programmed cell death 1 (PD-1) receptor. It has been approved by the FDA in patients with recurrent or metastatic cervical cancer with disease progression on or after chemotherapy whose tumors express the programmed cell death ligand 1 (PD-L1). Areas covered : Clinical studies of pembrolizumab in cervical cancer were analyzed and discussed. Data were obtained by searching for English peer-reviewed articles on PubMed, clinical trials registered on clincaltrials.gov and related abstracts on the ASCO meeting library. The aim was to review the status of pembrolizumab, the published and ongoing trials, and its safety and efficacy. Expert opinion : Pembrolizumab may ultimately represent a treatment of choice for advanced cervical cancer with PD-L1 expression, both in metastatic and recurrent setting. However, it is essential to better identify and characterize patients that will benefit the most.